2003
DOI: 10.4141/p02-033
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Canadian weeds. 124. Hydrocharis morsus-ranae L.

Abstract: Catling, P. M., Mitrow, G., Haber, E., Posluszny, U. and Charlton, W. A. 203. The biology of Canadian weeds. 124. Hydrocharis morsus-ranae L. Can. J. Plant Sci. 83: 1001-1016. European frog-bit (Hydrocharis morsus-ranae L.), a free-floating, stoloniferous aquatic, is native to Europe and parts of Asia and Africa. It was discovered in Canada in 1932 in Ottawa, but earlier introduction is possible. By 1955 its North American distribution extended from Ottawa to Montreal. By 1980 it had extended southwest to Lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…As stands containing H. morsus-ranae are developed in water rich in phosphates, total phosphorus content characterizes these conditions as hypertrophic [39]. The conditions reported in the literature as optimal for development of H. morsus-ranae can be mesotrophic [53,54], eutrophic [35,36,40,43,55] and hypertrophic [42,51,56], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 81%
“…As stands containing H. morsus-ranae are developed in water rich in phosphates, total phosphorus content characterizes these conditions as hypertrophic [39]. The conditions reported in the literature as optimal for development of H. morsus-ranae can be mesotrophic [53,54], eutrophic [35,36,40,43,55] and hypertrophic [42,51,56], which is in line with our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Those potential prey items were least abundant in the shading sites. The low abundance might be a consequence of low DO (Catling et al 2003, Zhu et al 2008 or low food availability, e.g., periphytic algae (Quinn et al 1997, Melody andRichardson 2004), associated with shading. Quinn et al (1997) studied a pasture stream for 142 d and found that total invertebrate and chironomid densities declined significantly as shade increased from 60 to 90% and invertebrate taxon richness declined markedly between 90 and 98% shade.…”
Section: Effects Of Hand Pulling and Shading Methodsmentioning
confidence: 97%
“…European frogbit is an aquatic perennial that propagates primarily by vegetative means. It can negatively affect native plants by obstructing light and may affect animals by displacing food plants and altering dissolved O 2 concentrations (Catling et al 2003, Zhu et al 2008. The species can block navigation channels, irrigation ditches, and water-intake pipes, and can reduce aesthetic and recreational value of water bodies, thereby decreasing tourism and real-estate values (Catling et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia it is present but scarce in Turkey, the Caucasus Mts, along the southern shore of the Caspian Sea and in south-western Siberia; isolated collections are reported from central Siberia and Kazakhstan, and in Africa from northernmost Morocco and Tunisia (Cook & Lüönd 1982, Hultén & Fries 1986, Timokhina 1988). In North America it escaped from cultivation in Ottawa in the 1930s, started to spread rapidly and currently is naturalized and a noxious weed in parts of Quebec, Ontario, Michigan, New York, Vermont and Washington (Catling et al 2003). In the Czech Republic H. morsus-ranae, a free-floating aquatic, grows in standing or very slowly flowing waters such as oxbow lakes, alluvial pools, shallow edges of fishponds with low-intensity management, and sheltered edges of slowly flowing rivers and drainage and irrigation channels, where it can form dense floating mats of interlocking plants.…”
Section: Gentianellamentioning
confidence: 99%